Experimental investigation of the bending clearance on the aerodynamic performance in turbine blade tip region. (15th April 2020) - Shuai, Jiang; Jianyang, Yu; Hongwu, Wang; Fu, Chen; Shaowen, Chen; Yanping, Song
Abstract: The bending clearance design method is applied for the aerodynamic optimization by using the Kriging model and Genetic Algorithm. To validate the effects of the clearance shape and the deformation coefficient on the TLF suppression, the baseline case and other four modified cases have been experimentally and numerically investigated in a low speed wind tunnel linear cascade. The measured data and numerical results demonstrates that the modified cases increase the pressure inside the clearance, impedes the tip leakage flow (TLF), and its deceleration effect on leakage fluid inside the bending clearance gradually increased with the increasing deformation coefficient. In addition, the presence of the blocking vortex (BV) exerts a brake on the tip leakage vortex (TLV) and divides it into two parts. The TLV development is interrupted in front of the midstream under the blocking effect, but the UPV scale is enlarged. Compared with the baseline case, the application of bending clearance is proved to reduce the aerodynamic loss and leakage with relative reduction of 9.7% and 28.8%, furthermore, the optimal configuration has better aerodynamic performance with relative reduction of 16.3% and 31%. Both of the aerodynamic loss and leakage continue to decline with the increase of λ, but no significant performance improvement will be achieved when λ exceeds 6 mm. Highlights: The bending clearance design method is applied by using the Kriging model and GA method. The experiments of the baseline and four modified cases were conducted in a turbine cascade. Optimal clearance configuration gained significant aerodynamic performance improvement. The BV altered the vortex system in tip region and divided the TLV into two parts. The loss and leakage continued to decline with the increase of λ.